Vanadate ion-catalyzed oxidation of methane with hydrogen peroxide in an aqueous solution - Romakh, Vladimir B.; Süss-Fink, Georg; Shul’pin, Georgiy B. (My University, 2008)
It was shown that, unlike methane oxidation with the reagent “hydrogen peroxide-vanadate anion-pyrazine-2-carboxylic acid (PCA)” in acetonitrile, the performance of the process in an aqueous solution is accompanied by the intense parallel degradation of the cocatalyst. Therefore, relatively high yields of methane oxidation products (largely, formic acid) cannot be attained unless a rather high PCA concentration is used. Admixtures of a strong acid (sulfuric, trifluoroacetic, or perchloric) increase the yield of the products. It was found that perchloric acid can also be used as a cocatalyst instead of PCA.